Subcortical functional connectivity alterations in first-episode medication-naïve adolescents with major depressive disorder. - Sun, Lei; Zhou, Zilin; Feng, Ruohan; Gao, Yingxue; Bao, Weijie; He, Hong; Li, Hongwei; Hu, Xinyue; Li, Hailong; Zhang, Lianqing; Huang, Guoping; Huang, Xiaoqi (European Child & Adolescent Psychiatry, 2025)
Major depressive disorder (MDD) demonstrates significant alterations in intrinsic functional connectivity (FC) of the subcortical networks (SCN). However, the neurobiological mechanisms underlying these changes in adolescents with MDD and their association with stressors and sleep disturbances remain poorly understood. Using seed-based functional connectivity analysis, we investigated changes in intrinsic connectivity of the SCN in 83 first-episode medication-naïve adolescents with MDD (aMDD) and 59 healthy controls (HC). We then examined the correlation between the SCN connectivity alterations with sleep disturbances and stress factors, measured by the Pittsburgh Sleep Quality Index (PSQI), the Adolescent Life Events Checklist (ASLEC), and the Family Environment Scale-Chinese Version (FES-CV). Compared with HC, aMDD patients showed decreased connectivity between multiple subcortical regions (amygdala, hippocampus, nucleus accumbens (NAc), and thalamus) and cortical regions of the limbic (orbital frontal cortex, inferior temporal gyrus, temporal pole), visual (middle occipital gyrus) and sensorimotor (precentral gyrus) networks. Moreover, we observed that reduced amygdala- and NAc-based FC was correlated with more stress from life events, while reduced thalamus-based FC was associated with more severe sleep disturbances. Our study was the first to comprehensively investigate the SCN-based FC alterations in adolescents with MDD. We revealed disruptions in connectivity between the SCN and cortical networks in aMDD, and further identified potential environmental mechanisms associated with these SCN-based dysconnectivity patterns. These findings underscore critical role of the SCN in the neurobiological mechanisms of aMDD and suggest potential targets for developing novel treatment strategies for adolescents with MDD.